A guide to the ALTF network. - Botwood, Lorayne; Cranney, Jacquelyn; Bennett, Dawn; Higgs, Joy; Kift, Sally; Oliver, Ron; Lee, Adrian (Office for Learning and Teaching, 2013)
Since the inception of the ALTC Fellowships in 2006, nearly 60 outstanding learning and teaching leaders in Australia have been recognised as Fellows. The Fellows have formed a network, the ALTC Fellows Alumni Association, which ensures members meet regularly in both face-to-face and virtual settings to provide support and leadership in higher education learning and teaching. This is a guide that introduces the ALTF network and its collaborative approach to supporting and promoting quality learning and teaching across Australian higher education.